7P Marketing Mix Drives Purchase and Repurchase at a Cafe - Triwardani, Agil; Safirin, Moch Tutuk (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid growth of the culinary industry in Indonesia has intensified competition among cafés, requiring effective marketing strategies to attract and retain consumers. Specific Background: D’Coffee Cup Merr Surabaya faces challenges in customer satisfaction, reflected in lower ratings compared to competitors, indicating the need to evaluate marketing factors influencing consumer behavior. Knowledge Gap: Previous studies on the 7P marketing mix show inconsistent findings, and limited research simultaneously examines its relationship with purchase decisions and repurchase behavior within a single Structural Equation Modeling framework. Aims: This study aims to analyze the relationship between the 7P marketing mix, purchase decisions, and repurchase behavior among café consumers. Results: The findings reveal that product significantly affects both purchase decisions and repurchase behavior, while price only influences purchase decisions; other variables such as place, promotion, process, and physical evidence show no significant relationship, and purchase decisions significantly drive repurchase behavior. Novelty: This study integrates all 7P variables within a single SEM model to provide a comprehensive understanding of direct and indirect relationships between marketing mix elements, purchase decisions, and repurchase behavior. Implications: The results highlight the importance of prioritizing product quality and variation in marketing strategies to strengthen consumer decisions and encourage repeat purchases in the competitive café industry. Highlights: Product-related factors dominate consumer behavior in both initial and repeat transactions. Price contributes only to initial buying decisions without extending to repeat actions. Consumer decision stage acts as a direct pathway toward repeated transactions. Keywords: Marketing Mix 7P, Purchase Decision, Repurchase, SEM